Low background scintillation setup to investigate radiopurity of materials - Kasperovych, D.V.; Danevich, F.A.; Kobychev, V.V.; Kropivyansky, B.N.; Sokur, N.V.; Tymoshenko, A.I. (Вопросы атомной науки и техники, 2018)
Background of 2.128 kg CdWO₄ scintillation detector was reduced by 3 orders of magnitude in the energy region 0.5…2.6 MeV, and one order of magnitude above 3 MeV in the low background scintillation setup located in the basement floor of a laboratory building at the Institute for Nuclear Research (Kyiv, Ukraine). It was achieved by application of radiopure passive shield, plastic scintillators to veto cosmic rays, and pulse-shape discrimination to reject fast Cherenkov signals in the quartz light-guide of the detector. Sensitivity of the setup to radioactive contamination of different materials were estimated. For instance, for a 3.36 kg titanium sample over 30 days of measurements detection limits are on the level of 2.9 mBq/kg (⁴⁰K); 0.6 mBq/kg (¹³⁷Cs); 2 mBq/kg (²²⁶Ra), and 0.5 mBq/kg (²²⁸Th).